2013
DOI: 10.1155/2013/760915
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Removal of Trace Steroid Hormones and Pharmaceuticals and Personal Care Products from Municipal Wastewater Using a Heterogeneous Fenton’s Catalytic Process

Abstract: The pollution of water sources by endocrine disrupting compounds (EDCs) and pharmaceutical and personal care products (PPCPs) is a growing concern, as conventional municipal wastewater treatment systems are not capable of completely removing these contaminants. A continuous stir tank reactor incorporating a modified polyacrylonitrile (PAN) catalyst and dosed with hydrogen peroxide in a heterogeneous Fenton’s process was used at pilot scale to remove these compounds from wastewater that has undergone previous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…A modified PAN catalyst system was effective in the removal of the target pollutants in WW, at ambient temperature and natural pH: > 80% of the estrogens were removed; > 84% of triclosan; 46-84.5% of carbamazepine; depending on the sampling location and consequent different characteristics of the WW effluents. [56] -Room temperature; natural pH.…”
Section: Photo-fentonmentioning
confidence: 99%
“…A modified PAN catalyst system was effective in the removal of the target pollutants in WW, at ambient temperature and natural pH: > 80% of the estrogens were removed; > 84% of triclosan; 46-84.5% of carbamazepine; depending on the sampling location and consequent different characteristics of the WW effluents. [56] -Room temperature; natural pH.…”
Section: Photo-fentonmentioning
confidence: 99%
“…The authors also observed complete decolourization of a pollutant in the optimal conditions. Chi et al 155 prepared a modied PAN ber by reacting 27.9 g PAN mesh with a 1 L solution of 49.6 g L À1 hydroxylamine sulphate and 23.17 g L À1 dihydrazine sulphate at pH 9.5, 100 AE 2 C under reux for 2 h with constant stirring. The authors used this heterogeneous Fenton catalyst for the removal of endocrine-disrupting compounds (EDCs) and pharmaceutical and personal care products (PPCPs) from municipal wastewater in a continuous stirred tank reactor.…”
Section: Iron and Iron Oxide-loaded Materialsmentioning
confidence: 99%
“…The degradation of BPA is shown in Figures 5 and 6. In Figure 5, a very fast degradation was achieved in less than 10 min of the catalytic reaction with an initial concentration of hydrogen peroxide corresponding to the theoretical amount of oxygen needed for the complete mineralisation of the BPA organic pollutant [36].…”
Section: Rotating Catalytic Reactormentioning
confidence: 99%